2022
DOI: 10.1155/2022/8305285
|View full text |Cite|
|
Sign up to set email alerts
|

GIS Multimedia Technology in Regional Construction Land Suitability Evaluation in Mountainous Villages and Towns

Abstract: In order to explore the suitability evaluation of regional construction land in mountainous villages and towns, a method based on GIS technology is proposed. Supported by GIS and RS technology, the Delphi method is used to determine the natural, socioeconomic, and ecological security factors affecting the ecological suitability of regional construction land in mountainous villages and towns, and analytic hierarchy process is used to calculate the weight of relevant influencing factors. Following the principle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%